FAKTOR–FAKTOR YANG BERHUBUNGAN DENGAN KADAR TIMBAL (PB) DALAM DARAH PADA SOPIR ANGKUTAN UMUM JURUSAN KARANG AYU-PENGGARON DI KOTA SEMARANG - Irimawa Rustanti; Eni Mahawati (Dian Nuswantoro Semarang, 2011)
Background: The cause of air pollution is smoke of motor vehicle. Public transportation represents one of transportation which releases the smoke. This condition cause public transport drivers always exposed by motor vehicle smoke that contain Plumbum and its health effect. The aim of this research is to examine Plumbum exposure and the factors that related with Plumbum concentration in blood of public transport drivers majors Karang Ayu-Penggaron in Semarang.Method: This is an explanatory research with the cross sectional approach. The population is 70 public transport drivers majors Karang Ayu-Penggaron and 34 samples selected by inclusion criteria. Data collected use the direct interview with questioner and laboratory test from the respondent’s blood sample. The variable in this research consist of age, work period, nutrition status, smoking habit, and Plumbum concentration in blood.Result: Based on the result of this research was known that the respondent characteristic’s are their age between 20-52 years old, their work period between 2-19 year, mean of IMT is 22,92 with the normal category nutrition status and 23 respondent have smoking habit. Theplumbum concentration in blood was 0,059 until 0,198 mg/liter. This concentration was similar with average of 12 cigarette smoked a day. The Pearson product moment correlation showed that there was significant correlation between age, work period, nutrition status, the smoking habit with the Plumbum concentration in blood, ñ-value is smaller than 0,05. Based on inferential analysis of the data was known that there was significant correlation between age, work period, nutrition status, the cigarette habit with the Pb concentration in blood. Suggestion for ORGANDA and the Head of Terminal Penggaron-Pedurungan Semarang should be applied the health inspection for public transport drivers and supply the mask for them. Public transport drivers should be using the mask correctly. Early prevention should be done by continuing measurement of the air Pb concentration by government, especially transportation department.Keywords: Plumbum Concentration, public transport drivers